The Role of Logistics Management in Hospital Services Peran Manajemen Logistik Dalam Pelayanan Di Rumah Sakit - Sri Wahyuni; Anggy Vidian; Budi Hartono; Nurfarahin Nurfarahin (LPPM Universitas Abdurrab, 2024)
To be able to support quality and good quality health services in hospitals, it is necessary to manage and manage tools/goods so that medical and non-medical equipment can be needed so that they are obtained quickly with sufficient quantities and good quality. Logistics management has a crucial role in hospital services. Logistics management plays an important role in improving the quality of medical services and patient satisfaction. This study aims to identify the role of logistics management in services in hospitals. Research Methods were carried out by searching the literature through the Google Scholar database with a population of journals and other sources relevant to the role of logistics management in the hospital. The data analyzed was in the form of secondary data, namely journal articles from previous research results published online in national journals. The included articles have maximum publications criteria of the last ten years. Based on a search of several articles, it was found that logistics management contributes to more timely and accurate decision-making, which in turn improves the operational efficiency of the Hospital. Logistics management can play an important role in improving the quality of health services and patient satisfaction. By optimizing logistics management so as to provide effectiveness and efficiency of logistics in hospitals.